2021
DOI: 10.1108/ijppm-11-2019-0535
|View full text |Cite
|
Sign up to set email alerts
|

ISO-9001 implementation and critical success factors of the Jordanian consulting engineering firms

Abstract: PurposeThis paper aims at studying the level of implementation of ISO 9001 in Jordanian consulting engineering firms and to what extent does the implementation effectiveness affect the success of the construction projects. Moreover, the paper seeks to identify the Critical Success Factors (CSFs) that directly influence the ISO 9001 effectiveness in Jordanian consulting engineering firms.Design/methodology/approachA questionnaire was constructed and distributed to a sample of 125 employees from six ISO 9001-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…This barrier was mainly related to the issue of generating a large quantity of information during construction, but without having the effective management of this information, or without generating learning lessons for the future projects [21,61,65,110,111]. The significance of this barrier can be explained by the lack of the culture of the continuous improvement in the Jordanian construction industry as discussed in the studies of Sweis, et al [31] and Albalkhy and Sweis [33] who found low levels of the continuous improvement culture among the Jordanian construction contractors, and Sweis, et al [112] who found similar results among the Jordanian construction consultants who are certified with ISO-9001.…”
Section: Discussionmentioning
confidence: 99%
“…This barrier was mainly related to the issue of generating a large quantity of information during construction, but without having the effective management of this information, or without generating learning lessons for the future projects [21,61,65,110,111]. The significance of this barrier can be explained by the lack of the culture of the continuous improvement in the Jordanian construction industry as discussed in the studies of Sweis, et al [31] and Albalkhy and Sweis [33] who found low levels of the continuous improvement culture among the Jordanian construction contractors, and Sweis, et al [112] who found similar results among the Jordanian construction consultants who are certified with ISO-9001.…”
Section: Discussionmentioning
confidence: 99%
“…The current study used the quantitative approach using a questionnaire to collect quantitative data to achieve its objectives. The use of the quantitative approach is very common in managerial studies since it gives the researcher quantitative insights into the perceptions of individuals in the organizations [49][50][51]. Accordingly, it is useful to assess the satisfaction of employees as occupants of the buildings.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a combined sample of 23 organisations, including the primary data from six organisations and the secondary data from seventeen organisations, is evaluated. Research on quality management system performance using same six numbers of organisations is previously available (Sweis et al ., 2022). Castka (2018), for a study of ISO 9001 certified firms, used a sample size of 15.…”
Section: Research Gaps and Research Approachmentioning
confidence: 99%